LEGAL PROTECTION FOR CONSUMERS IN SHOPEE E-COMMERCE ONLINE BUYING AND SELLING IS REVIEWED FROM LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Fadhlillah Febrian; Hamdan Azhar Siregar (Adisam Publisher, 2026)
Legal protection for consumers in Shopee e-commerce online buying and selling is reviewed from Law No. 8 of 1999 on Consumer Protection. Electronic Commerce or e-commerce is one of the products of the times. This type of business transaction provides convenience and has many advantages compared to conventional or offline transactions. Consumer protection laws provide protection for consumers in Indonesia. Conflicts between business actors are based on unexpected things by consumers beforehand. The weak position of consumers with business actors in conducting online transactions is certainly very detrimental to consumers. Crimes in online media against the purchase and sale of products in the premises are the same as the crime of fraud. Conventional and online buying and selling differ only in the means of action, namely using an Electronic System. The purpose of this study is to find out how the law in Indonesia provides protection to consumers and how efforts are made by the government in developing or updating legal protection for consumers who make transactions through Shopee e- commerce. This study uses normative law research methods. Using a statute approach and a conceptual approach. Law Number 8 of 1999 (UUPK), Law Number 19 of 2016 (ITE Law) and Law as primary law. Secondary legal materials use books containing consumer protection, electronic trading books and utilize journals and articles that can be downloaded through websites available online. The results of this study discuss legal protection for consumers in conducting online transactions from the perspective of Law Number 8 of 1999 concerning Consumer Protection. The online transaction process has a distinctive characteristic where the medium used is the internet so that business actors and consumers do not meet directly. On the one hand, this condition is very beneficial for consumers, because consumers have many options to get the goods they buy, but on the other hand, violations of consumer rights are very risky, therefore legal protection for consumers in online transactions is needed.